An investigative study for the prediction of compressive strength of cement-clay interlocking (CCI) hollow brick masonry walls. (June 2022) - Joyklad, Panuwat; Ali, Nazam; Yooprasertchai, Ekkachai; Jaffar, Syed Taseer Abbas; Magbool, Hassan M.; Hussain, Qudeer; Chaiyasarn, Krisada
Abstract: Masonry structures are used in many parts of the world because of their varying benefits of being low-cost, heat insulations, local availability, and skilled labor. Therefore, to investigate the compressive stress-strain behavior and detailed analysis and assessment of masonry structures made of CCI bricks is imperative. Axial compressive results of 10 hollow cement-clay interlocking (CCI) bricks made masonry walls are presented. 10 masonry walls were tested under concentric compressive load in 2 groups. Bricks of each group had different compressive strength. Five walls in each group comprised of 1 control wall (ungrouted), 1 wall grouted with Ordinary Portland Cement (OPC), 1 wall grouted with non-shrink (NS) cement, 1 wall grouted with OPC and strengthened by steel bars, and 1 wall grouted with NS and strengthened with steel bars. Among 5 walls in each group, control wall created the lower bound in terms of the peak load sustained. While the upper bound was created by the wall grouted with NS cement and further strengthened by steel bars. It was found that the addition of grout (irrespective of its type) significantly improved the peak compressive load. However, increase in peak load over that of the control wall was associated to the grout type. Walls grouted with NS cement attained higher peak loads as compared to those grouted with OPC. It was observed that the addition of cement grout does not guarantee a ductile post-peak behavior. Addition of steel bars not only increased the peak loads, but it also improved the post peak behavior. Accuracy of existing compressive load analytical models was assessed, and it was found that none of the analytical models considered were able to predict close approximations. A linearly regressed model is proposed to predict compressive strength of CCI brick masonry walls with good accuracy.